Ibtikāru taqwīmi al-mahārāti al-istiqbāliyyati fī al-lughati al-‘Arabiyyati al-qāʾimi ‘alā manṣati Kuīzīz (Quizizz) fī kitābi al-lughati al-‘Arabiyyati liṣ-ṣaffi ath-thālithi (KMA 2020) - Hikmal Akbar; Ahmad Riyadissolihin; R. Umi Baroroh; Fatin Natasya Binti Hasan Ashari (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2026)
This study aims to develop an assessment instrument for Arabic receptive skills based on the Quizizz platform for third-grade students at Islamic elementary schools (madrasah ibtidaiyah) in accordance with KMA 2020. The method employed is Research and Development (R&D) using the ADDIE model, implemented up to the development stage. The development process began with a needs analysis of the curriculum, student characteristics, and current assessment practices, followed by the design of item grids and the development of 48 test items comprising 20 audio-based listening items and 28 reading items supported by texts and images. Validation was conducted by three validators consisting of a content expert, an evaluation expert, and a media expert. The validation results yielded an average score of 88.55%, classified as highly feasible. The instrument integrates multimedia and gamification features of Quizizz, including audio, visual illustrations, a point system, leaderboard, timer, and automatic feedback, making the assessment more interactive, engaging, and efficient. In conclusion, the Quizizz-based assessment instrument meets the criteria of content validity, construct validity, and media feasibility, making it a viable alternative for Arabic language learning assessment in the digital era.